THE EFFECT OF ATTITUDE, SUBJECTIVE NORMS AND CONTROL OF BEHAVIOR TOWARDS INTENTION IN SHARE INVESTMENT - Erna Retna Rahadjeng; Yulist Rima Fiandari (Universitas muhammadiyah malang, 2020)
The development of the stock market has been dominated by individual. The decision-making process in investment actions is influenced by various individual characteristics and systematic factors are important elements that have an important influence on investors' financial decision making. Stock purchases can be influenced by attitudes, subjective norms and biases from past experiences. Stock investment is starting to be of interest to scholars. This study aims to determine and analyze the effect of attitudes, subjective norms and behavioral control on investment intentions in the capital market. The population that will be used as the research object is scholars in Malang, who have already been familiar with finance courses. The sampling method used was purposive sampling, namely determining the sample according to the research objectives. Data analysis is used to determine the effect of independent variables on the dependent variable, which is analyzed using path analysis with PLS. The result show that attitudes, subjective norms and behavioral control have an influence on the intention to invest in shares investment.